Vancomycin Associated Acute Kidney Injury: A Longitudinal Study in China - Kunming, Pan; Can, Chen; Zhangzhang, Chen; Wei, Wu; Qing, Xu; Xiaoqiang, Ding; Xiaoyu, Li; Qianzhou, Lv (Frontiers in Pharmacology, 2021)
Background Vancomycin-associated acute kidney injury (VA-AKI) is a recognizable condition with known risk factors. However, the use of vancomycin in clinical practices in China is distinct from other countries. We conducted this longitudinal study to show the characteristics of VA-AKI and how to manage it in clinical practice. Patients and Methods We included patients admitted to hospital, who received vancomycin therapy between 1 January 2016 and June 2019. VA-AKI was defined as a patient having developed AKI during vancomycin therapy or within 48 hours following the withdrawal of vancomycin therapy. Results A total of 3719 patients from 7058 possible participants were included in the study. 998 patients were excluded because of lacking of serum creatinine measurement. The incidence of VA-AKI was 14.3%. Only 32.3% (963/2990) of recommended patients performed therapeutic drug monitoring (TDM) of vancomycin. Patients with VA-AKI were more likely to concomitant administration of cephalosporin (OR 1.55, 95% CI 1.08-2.21, P=0.017), carbapenems (OR 1.46, 95% CI 1.11-1.91, P=0.006) and piperacillin-tazobactam (OR 3.12, 95% CI 1.50-6.49, P=0.002). Full renal recovery (OR 0.208, p=0.005) was independent protective factors for mortality. Compared with AKI stage 1, AKI stage 2 (OR 2.174, p=0.005) and AKI stage 3(OR 2.210, p=0.005) were independent risk factors for fail to full renal recovery. Conclusions Lack of a serum creatinine measurement for the diagnosis of AKI and lack of standardization of vancomycin therapeutic drug monitoring should be improved. Patient concomitant with piperacillin-tazobactam are at higher risk. Full renal recovery was associated with a significantly reduced morality.